Chemical Constituents and Evaluation of Bioactivity of Vernonia hymenolepis A. Rich Root Extracts - Gelata, Alemu; Jemal, Mudin; Gershe, Soressa; Abdissa, Negera (Biology, Medicine, & Natural Product Chemistry, 2024)
The medicinal herb Vernonia hymenolepis has been used to cure a wide range of ailments such as cancer, gonorrhea, stomach ache, malaria, hepatitis, pneumonia, toothache, diarrhea, amoebiasis, typhoid, hypertension, and constipation by diverse societies in Ethiopia, Kenya, and Tanzania. However, its biological and phytochemical data is extremely insufficient. Thus, the aim of this research work was to study the chemical constituents and antimicrobial activity of the root part of this plant. The roots of plant were dried by air under shade and then successively extracted with chloroform and methanol. The chloroform root extract was subjected to silica gel column chromatographic separation which gave two compounds, namely; betulinic acid (1) and 2-hydroxy-3-(4-hydroxyphenyl)-2-propenoic acid (2). The structures of the isolated compounds were elucidated using 1H and 13C NMR spectroscopic techniques and by comparing with literature reports. The crude extracts were assayed in vitro employing disc diffusion technique against four bacterial strains (Bacillus subtilis ATCC11778, Staphylococcus aureus ATCC25923, Escherichia coli ATCC25922, and Pseudomonas aeruginosa ATCC27853) and one fungal strain (Candida albicans ATCC 10231). Significant antibacterial activity was demonstrated by the crude extracts; with the chloroform extract exhibiting greater activity against Escherichia coli (18 mm) when compared to gentamicin (25 mm). The methanol extract revealed the highest activity (13 mm) against Candida albicans with the reference drug, clotrimazole showing an inhibition zone of 12 mm. The antimicrobial activity exhibited by root extracts of V. hymenolepis corroborates its traditional use against bacterial diseases.